Altered Outer Membrane Transcriptome Balance with AmpC Overexpression in Carbapenem-Resistant Enterobacter cloacae - Majewski, Piotr; Wieczorek, Piotr; Ojdana, Dominika; Sieńko, Anna; Kowalczuk, Oksana; Sacha, Paweł; Nikliński, Jacek; Tryniszewska, Elżbieta (Frontiers in Microbiology, 2016)
The growing incidence of multidrug-resistant (MDR) bacteria is an emerging challenge in modern medicine. The utility of carbapenems, considered “last-line” agents in therapy of infections caused by MDR pathogens, is being diminished by the growing incidence of various resistance mechanisms. Enterobacter cloacae have lately begun to emerge as an important pathogen prone to exhibiting multiple drug resistance. We aimed to investigate the molecular basis of carbapenem-resistance in 44 E. cloacae clinical strains resistant to at least one carbapenem, and 21 susceptible strains. Molecular investigation of 65 E. cloacae clinical strains was based on quantitative polymerase chain reaction (qPCR) allowing for amplification of ampC, ompF, and ompC transcripts, and analysis of nucleotide sequences of alleles included in MLST scheme. Co-operation of three distinct carbapenem resistance mechanisms has been reported – production of OXA-48 (5%), AmpC overproduction (97,7%), and alterations in outer membrane (OM) transcriptome balance. Carbapenem-resistant E. cloacae were characterized by (1.) downregulation of ompF gene (53,4%), which encodes protein with extensive transmembrane channels, and (2.) the polarization of OM transcriptome-balance (79,1%), which was sloped towards ompC gene, encoding proteins recently reported to possess restrictive transmembrane channels. Subpopulations of carbapenem-susceptible strains showed relatively high degrees of sequence diversity without predominant types. ST-89 clearly dominates among carbapenem-resistant strains (88,6%) suggesting clonal spread of resistant strains. The growing prevalence of pathogens resistant to all currently available antimicrobial agents heralds the potential risk of a future “post-antibiotic era.” Great efforts need to be taken to explore the background of resistance to “last resort” antimicrobials.